A novel kisspeptin antagonist peptide 234 prevents kisspeptin-induced pubertaladvancement in the female rats - Ozcan, M.; Sahin, Z.; Canpolat, S.; Yilmaz, B.; Kelestimur, H. (Wiley-Blackwell, 2014)
[Abstract Not Available]